Strategic Analysis of PT Kalbe Farma, Tbk. (KLBF) - Melina Melina (Dinasti Publisher, 2025)
This study analyzes the business strategy of PT Kalbe Farma, Tbk (KLBF) in addressing the dynamics of the national and global pharmaceutical industry. The analysis was conducted using a strategic management approach through IFE, EFE, CPM, SWOT, SPACE, BCG, IE, Grand Strategy, and QSPM matrices. Based on the analysis, the priority strategies recommended for KLBF are market penetration, product development, market development, and both horizontal and vertical integration, with a focus on the prescription drug and nutrition divisions. Strategy implementation emphasizes strengthening research, developing value-added products, eco-friendly operational efficiency, digitalization, and international market expansion. These findings highlight the importance of synergy among innovation, efficiency, and digitalization to enhance KLBF’s competitiveness.